Enhancement of the antimycobacterial activity of macrophages by ajoene. Issue 1 (January 2018) - Choi, Ji-Ae; Cho, Soo-Na; Lim, Yun-Ji; Lee, Junghwan; Go, Dam; Kim, Seon-Hwa; Song, Chang-Hwa
Ajoene, a garlic-derived sulfur-containing compound, has broad-spectrum antimicrobial activity. To assess the potential of ajoene for treating tuberculosis (TB), we determined whether it induces the stress response of the endoplasmic reticulum (ER), which plays an important role in TB. We showed that ajoene stimulation induced the production of ER stress sensor molecules and reactive oxygen species (ROS) levels. Ajoene-induced ROS production was dependent on c-Jun N-terminal kinase (JNK) activation. Interestingly, the inhibition of JNK activity and suppression of ROS production reduced ajoene-induced CHOP production in macrophages. Because ER stress activates autophagy, the activation of which suppresses the growth of mycobacteria, we investigated the ajoene-induced production of autophagy-related factors, including LC3-II, P62 and Beclin-1. As expected, ajoene treatment increased the levels of these factors in RAW 264.7 cells. Remarkably, the total amount of Mycobacterium tuberculosis (Mtb) H37Rv was significantly reduced in ajoene-treated RAW 264.7 cells. The treatment of macrophages with ajoene resulted in the activation of JNK, induction of ROS synthesis and accumulation of ROS, possibly leading to the activation of ER stress and autophagy. These results reveal the mechanism of the antimycobacterial effects of ajoene against Mtb H37Rv. Our findings might facilitate the development of novel therapies for patients with TB.